1990
DOI: 10.1002/jso.2930440416
|View full text |Cite
|
Sign up to set email alerts
|

Extrapericardial tamponade with herniated omentum after transhiatal esophagectomy

Abstract: An unusual complication following transhiatal esophagectomy for lower esophageal carcinoma is reported in which extrapericardial tamponade and profound shock occurred secondary to a herniated section of omentum in the immediate postoperative period. The two-dimensional echocardiogram was nondiagnostic, but the diagnosis was confirmed during reexploration of the abdomen. Anatomic and pathophysiologic considerations of this unusual but life-threatening complication are discussed. The literature suggests that com… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
6
0

Year Published

2001
2001
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 15 publications
(6 citation statements)
references
References 6 publications
0
6
0
Order By: Relevance
“…In our institution, the mediastinal route is preferred after esophagectomy, and incidence of diaphragmatic herniation after esophagectomy was 1% (2/168). To date, 30 cases of diaphragmatic herniation after esophagectomy for carcinoma of the esophagus have been reported in the English-language literature (Table 1) [2][3][4][5][6][7][8][9][10][11][12][13]. Our reports of diaphragmatic herniation after esophagectomy are, to our knowledge, the fi rst from Japan in the English-language literature.…”
Section: Discussionmentioning
confidence: 59%
“…In our institution, the mediastinal route is preferred after esophagectomy, and incidence of diaphragmatic herniation after esophagectomy was 1% (2/168). To date, 30 cases of diaphragmatic herniation after esophagectomy for carcinoma of the esophagus have been reported in the English-language literature (Table 1) [2][3][4][5][6][7][8][9][10][11][12][13]. Our reports of diaphragmatic herniation after esophagectomy are, to our knowledge, the fi rst from Japan in the English-language literature.…”
Section: Discussionmentioning
confidence: 59%
“…Furthermore, cases of isolated left atrial compression resulting in respiratory symptoms have been reported in association with a variety of mediastinal pathology, including bronchogenic cysts, carcinomas, thymomas, and aortic aneurysms [16]. Gastroesophageal conditions, such as hiatal hernias with gastric volvulus [17,18] and two reports of herniated omentum [19], have led to extrapericardial cardiac compression post-operatively.…”
Section: Discussionmentioning
confidence: 98%
“…Granke et al . have observed omental herniation through the hiatus 7days after surgery 7 . Katariya et al.…”
Section: Discussionmentioning
confidence: 98%